THE RISK ASSOCIATED WITH THE ONE-PARTNER AUDIT TEAM SCENARIO: A PRELIMINARY STUDY - Al-Adeem, Khalid R. (UI Scholars Hub, 2023)
An accounting firm may bear the risk associated with the partner supervising the engagement. This study aims to explore the dynamics within the audit engagement to illustrate the potential consequences of the partner's actions and decisions that extend beyond the firm. A synthesis of three theories, namely functional organization theory, the power of lower participants theory, and the third dimension of power theory, reveals the power distribution between the partner leading the audit engagement and other participating auditors. While the functional organization theory and the second and third dimensions of power theory suggest that the lead partner holds more power, the power of lower participants theory proposes that lower-level auditors can influence outcomes in conflicts. A web-based survey with 66 auditors was conducted to gather insights. While not all hypotheses find support in the data, the study uncovers interesting aspects of the auditor-partner relationship. These findings have significant implications for how audit engagements are organized and warrant further exploration. Auditors generally accept the partner's justifications regarding suspicious transactions and accounting treatments but refrain from sharing specific information. They believe in the importance of audit partners' awareness of gathered information. Although auditors do not fear repercussions when reporting wrongdoing, they tend not to report to local authorities. However, they endorse the idea of appointing a reviewing partner, quality assurance, or risk control role to mitigate errors in the audit process.